The Discussion of aoInfanta Problem: The Situation and Trends of Chinese Childrens Animation (Global Journal of Human-Social Science, 2015)
The problem "Infant" in Chinese animation will be analyzed, the differences between Chilren's Animation and "Infant" will be declaired, then it will be point out that Childish view in Chinese public opinion is wrong. There are shown that the Chinese animation's experiences and trends.
Keywords: chinese children2019; s animation; infant; trends